2011
DOI: 10.1021/jp112053b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Rb2 in HeN: Potential Energy Surface and Monte Carlo Simulations

Abstract: An analytical potential energy surface for a rigid Rb₂ in the ³Σ(u)⁺ state interacting with one helium atom based on accurate ab initio computations is proposed. This 2-dimensional potential is used, together with the pair approximation approach, to investigate Rb₂ attached to small helium clusters He(N) with N = 1-6, 12, and 20 by means of quantum Monte Carlo studies. The limit of large clusters is approximated by a flat helium surface. The relative orientation of the dialkali axis and the helium surface is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 70 publications
7
47
2
Order By: Relevance
“…Our smaller binding energy for this complex can be explained in terms of their slightly deeper PES, with a ratio of the potential well minima of 2.59 (Guillon et al)/2.342 (this work) = 1.1. With regard to N = 2 the results of Guillon et al do not follow the IPM and E(He 2 Rb 2 ) ∼ 3 × E(HeRb 2 ), in accordance with their description of the He 2 Rb 2 system given in ref 25: a packed configuration of the two rare-gas atoms with the resulting large interaction energy. However, it is in contrast with both the same VAR and DMC picture found in this work and other studies with a very similar impurity like Cs 2 , 18,19 where a crosslike structure is observed with the ensuing fulfillment of the IPM.…”
Section: Larger Complexessupporting
confidence: 75%
“…Our smaller binding energy for this complex can be explained in terms of their slightly deeper PES, with a ratio of the potential well minima of 2.59 (Guillon et al)/2.342 (this work) = 1.1. With regard to N = 2 the results of Guillon et al do not follow the IPM and E(He 2 Rb 2 ) ∼ 3 × E(HeRb 2 ), in accordance with their description of the He 2 Rb 2 system given in ref 25: a packed configuration of the two rare-gas atoms with the resulting large interaction energy. However, it is in contrast with both the same VAR and DMC picture found in this work and other studies with a very similar impurity like Cs 2 , 18,19 where a crosslike structure is observed with the ensuing fulfillment of the IPM.…”
Section: Larger Complexessupporting
confidence: 75%
“…The stability of the He N Ca systems studied here has been analyzed in terms of the corresponding pure He N clusters. Since a great deal of interest is usually manifested in the energetics and dynamics of doped clusters when the number of He atoms is modified, we clearly see in Figures and the energy of the doped clusters increases with N . Therefore, the evaporation or ejection of the He atoms from the He N Ca system at a constant value of T has to be understood as a loss of stability of the entire cluster.…”
Section: Discussionmentioning
confidence: 78%
“…A two-dimensional potential energy surface for a rigid Rb 2 molecule ( 3 + u ) interacting with a helium atom has been recently proposed in Ref. 22. It was used to study the structure and the energetics as well as the rotational dynamics of Rb 2 treated as a rigid dimer attached to small 4 He clusters and films.…”
Section: Introductionmentioning
confidence: 99%